Eksistensi Perempuan dalam Novel Laut Bercerita Karya Leila S. Chudori: Kajian Feminisme Eksistensialis dan Relevansinya sebagai Materi Ajar Sastra Indonesia di SMA - Dinda Anggraini Ginting; Achmad Yuhdi (Pusat Riset dan Inovasi Nasional, 2023)
The struggle of women in maintaining their existence is increasingly being voiced. One of the media that is often used is literari works. Given this, the aim of this research is to describe the existence of women amid male domination in Leila S. Chudori’s novel Laut Bercerita. This study uses a qualitative approach to examine the forms of existentialist feminism contained in the novel Laut Bercerita. This study took data in the form of text and utterances conveyed by each character. Data was collected using the 4M technique, namely reading, understanding, taking notes, and concluding. The result of this study is the discovery of Simone de Beauvoir,s feminist existence through the three female characters in the novel, namely Kasih Kinanti, Ratih Anjani, and Asmara Jati. Related to this, the results of the analysis of the existence of feminism based on Simone de Beaviour’s theory are relevant to be submitted as material in teaching Indonesian in class 11 high school, especially in material analysis of literary works.